Preparing Preservice Teachers to Teach Young Adult Literature in Conservative Contexts - Megan M. Van Deventer (University of Oklahoma Libraries, 2023)
Requests to censor or ban young adult literature from K-12 classrooms and curricula have increased. Especially in conservative states and contexts, censorship challenges are systematic and unrelenting, with coordinated campaigns from administrators, parents, and other educational stakeholders. Therefore, English Education must prepare and empower preservice teachers to read, teach, and advocate for the inclusion of diverse young adult literature in their school communities. This article details the pedagogical design of a methods course that instructs preservice English teachers to strategically navigate and counter this conservative activism to protect adolescents' access to young adult literature.